METODE HIRARC DALAM UPAYA MEMPERKECIL RISIKO KECELAKAAN KERJA DAN USULAN PERBAIKAN SISTEM K3 DI CV. ABADI JAYA PRESISI - Aditya Kurniawan Akh. Sokhibi (Universitas Muria Kudus, 2021)
CV Abadi Jaya Presisi is a company engaged in manufacturing the manufacture of household appliances made of plastic such as wakul, plastic jar, plastic spoon and rollers. Hazard Identification, Risk Assessment and Risk Control (HIRARC) is a way to find out the dangers that exist in CV Abadi Jaya Presisi. The research method used is HIRARC, with data collection techniques namely observation and interviews. The results of the study found that 4 operations were in condition N/ according to the procedure and A/ outside the procedure, 1 operation was in condition E/ difficult to control. With the value obtained from the research the risk of work accidents is in a condition of medium and small risk. By controlling risks such as wearing gloves to avoid slashing hands and hot finished products, using eye protection equipment, checking cranes regularly, using a helmet to avoid hitting the head with hard objects, checking electrical installations, using ear protective equipment and masks when operating. Crusher machine, and use safety shoes when installing and removing molds. For Personal Protection equipment, it should be provided at work locations because there is a lack of Personal Protection in the work area